(untitled) (Journal of Economics and Sustainability, 2021)
Job-education mismatch and overeducation issues among graduates have been discussed extensively, specifically related to the incidents, determinants, methods of measurement, and the effects of the mismatch. Despite this, the concept of job-education mismatch itself is not clearly explained. Since understanding this concept has theoretical and practical implications, this paper provides a critical review of the job mismatch concept and relates it to overeducation, which is a type of job-education imbalance under a vertical mismatch. This study relies solely on the literature review and does not provide any empirical evidence related to these concepts. A few issues have been highlighted and worth considering for further deliberation. Firstly, even though job-education mismatch, overeducation, overqualification, and underemployment are interchangeably used, these concepts have quite a distinct meaning. Secondly, when individuals’ skills are considered in discussing vertical and horizontal mismatch, the scope of mismatch tends to be broader than that of overeducation. Thirdly, the discussion on overeducation tends to concentrate on the level of study imbalance and not on both the level and type of study. Fourthly, job-education imbalance by the field of study (horizontal mismatch) is not easily defined, and the discussion tends to be related to overeducation. Received 16 May 20. Revised 27 Jul 20. Accepted 2 August 20.